Field-friendly anti-PGL-I serosurvey in children to monitor Mycobacterium leprae transmission in Bihar, India - Pierneef, Louise; Malaviya, Paritosh; van Hooij, Anouk; Sundar, Shyam; Singh, Abhishek Kumar; Kumar, Rajiv; de Jong, Danielle; Meuldijk, Maaike; Kumar, Awnish; Zhou, Zijie; Cloots, Kristien; Corstjens, Paul; et al. (Frontiers in Medicine, 2023)
Background: It has been amply described that levels of IgM antibodies against Mycobacterium leprae (M. leprae) phenolic glycolipid I (PGL-I) correlate strongly with the bacterial load in an infected individual. These findings have generated the concept to use seropositivity for antibodies against M. leprae PGL-I as an indicator of the proportion of the population that has been infected. Although anti-PGL-I IgM levels provide information on whether an individual has ever been infected, their presence cannot discriminate between recent and past infection. Since infection in (young) children by definition indicates recent transmission, we piloted the feasibility of assessment of anti-PGL-I IgM seroprevalence among children in a leprosy endemic area in India as a proxy for recent M. leprae transmission. Material and methods: A serosurvey for anti-PGL-I IgM antibodies among children in highly leprosy endemic villages in Bihar, India was performed, applying the quantitative anti-PGL-I UCP-LFA cassette combined with low-invasive, small volume fingerstick blood (FSB). Results: Local staff obtained FSB of 1,857 children (age 3 – 11 years) living in 12 leprosy endemic villages in Bihar. 215 children (11.58%) were seropositive for anti-PGL-I IgM. Conclusions: The anti-PGL-I seroprevalence level of 11.58% among children corresponds with the seroprevalence levels described in studies in other leprosy endemic areas over the past decades where no prophylactic interventions have taken place. The anti-PGL-I UCP-LFA was found to be a low-complexity tool that could be practically combined with serosurveys and was well accepted by both health care staff and the population. On route to leprosy elimination, quantitative anti-PGL-I serology in young children holds promise as a strategy to monitor recent M. leprae transmission in an area.